Patient, Caregiver, and Provider Perspectives on Improving Provider-Patient Interactions in Hemodialysis: A Qualitative Study - Melanie D. Talson; Priscila Ferreira da Silva; Juli Finlay; Krista Rossum; Kaytlynn V. Soroka; Michael McCormick; Arlene Desjarlais; Hans Vorster; Rachelle Sass; Matthew James; Manish M. Sood; Allison Jaure; et al. (Canadian Journal of Kidney Health and Disease)
Background: Improving interactions between people receiving hemodialysis and health care providers of facility-based hemodialysis care is a top priority for patients, caregivers, and health care providers. Objective: To identify challenges for high-quality clinical interactions in facility-based hemodialysis care as well as potential solutions. Design: Multicentre qualitative study using focus groups and semi-structured interviews to elicit the perspectives of patients, caregivers, and health care providers. Setting: Five Canadian facility-based hemodialysis centers. Participants: English-speaking adults receiving facility-based hemodialysis for longer than 6 months, their caregivers, and hemodialysis health care providers. Methods: Between May 2017 and August 2018, focus groups and interviews with patients and their caregivers subsequently informed semi-structured interviews with providers. Data were analyzed using inductive thematic analysis with application of a grounded theory approach. Results: A total of 8 focus groups and 44 interviews were completed. Participants included 64 people receiving hemodialysis, 18 caregivers, and 31 health care providers. Communication between health care providers and patients was often characterized as intersections of care (unidirectional) rather than interactions (bidirectional). Challenges were grouped into 4 main themes as follows: (1) culture of care provision; (2) mistrust between patients and health care providers; (3) time constraints for clinical interactions, and (4) lack of collaboration and care coordination among health care team. Potential solutions were identified for each challenge. Limitations: Findings were limited to Canadian context, English-speaking adults, and individuals receiving facility-based hemodialysis in urban centers. Conclusions: Interactions between health care providers and people receiving dialysis are often unidirectional, where the patient is a passive recipient of ideas and information from the health care provider. To promote improved bidirectional interactions, team-based care that includes better tools to improve information transfer, better information regarding roles, and identity of health care team members and opportunities for all members of the health care team, including the people receiving dialysis, to provide input on care plans is required. Trial Registration: Not applicable.